DECISION SUPPORT SYSTEM MENGGUNAKAN FUZZY LOGIC PADA PERSEROAN TERBATAS SAPTA INDRA SEJATI DIVISI GENERAL SUPPORT TRANSPORT - Mega Orina Fitri; Herni Herni (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2015)
t’s not easy to implement Decision Support System (DSS)application in a company. There are many things need to be consideredbefore a manager take a decision. And there are a few methods can be usedto implement DSS applicaton.. This paper explained about how to make aDSS application by using Fuzzy Logic. The case took place in GeneralSupport Divison at PT Sapta Indra Sejati, Kalimantan Selatan. This DSS isusing Fuzzy DatabaseTahanis’Model (Fuzzy Tahani).Data is obtained fromlibrary research and interviews. A Data Warehouse will be built beforedesain a DSS application. This application will be tested by using BlackBoxTesting. The result of this testing is the application can perform well andreliable to give recommendations to help manager to take a decision for thecompany quickly.